Is Cryocide an Ethically Feasible Alternative to Euthanasia? - Andrade, Gabriel; Redondo, Maria Campo (Journal of Medicine & Philosophy, 2024)
While some countries are moving toward legalization, euthanasia is still criticized on various fronts. Most importantly, it is considered a violation of the medical ethics principle of non-maleficence, because it actively seeks a patient's death. But, medical ethicists should consider an ethical alternative to euthanasia. In this article, we defend cryocide as one such alternative. Under this procedure, with the consent of terminally-ill patients, their clinical death is induced, in order to prevent the further advance of their brain's deterioration. Their body is then cryogenically preserved, in the hope that in the future, there will be a technology to reanimate it. This prospect is ethically distinct from euthanasia if a different criterion of death is assumed. In the information-theoretic criterion of death, a person is not considered dead when brain and cardiopulmonary functions cease, but rather, when information constituting psychology and memory is lost.